Polymer and application thereof
By developing a specific polymer, the shear resistance of CO2/water foam is enhanced, and the problem of insufficient shear resistance of existing foam oil repellents during flow is solved, which significantly improves oil recovery.
Patent Information
- Application Number
- CN202411712753.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing CO2 foam oil repellent has insufficient shear resistance during flow, resulting in low recovery.
Develop a polymer that enhances the shear resistance of CO2/water foam by specific monomer solution composition and preparation methods. The preparation method of the polymer includes using monomers such as 2-acrylamide-2-methylpropanesulfonic acid, vinyl acetate, vinylpyrrolidone, acrylamide or dimethylaminopropylacrylamide, cosolvent, initiator and reducing agent, to obtain a polymer with high viscosity and shear resistance by controlling reaction conditions such as temperature and time.
The viscosity and shear resistance of foam oil repellent are significantly improved, and the stability and impact efficiency of foam when flowing in heterogeneous formations are enhanced, thereby improving oil recovery.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polymer and application thereof. Background Art
[0002] The foam in the foam flooding agent usually refers to the structure formed by the uniform dispersion of the gas phase in water under the action of surfactants. CO2 foam flooding agent has a higher viscosity than water and CO2. Under the action of the Jamin effect, it can solve problems such as gravity segregation, viscous fingering and gas channeling, significantly improve oil recovery and achieve CO2 storage. The selection of suitable foaming agents and stabilizers is crucial to the performance of CO2 foam flooding agents. Cocoamidopropyl betaine, as a zwitterionic surfactant, has good foaming properties and the generated foam has good stability. It has been widely used in the field of improving oil field recovery. Adding a suitable polymer to the CO2 foam system can significantly increase the viscosity of the foam while improving the stability of the foam, further improving the recovery rate of the foam flooding agent.
[0003] It is worth noting that bulk foam in a static state has different properties from fluid foam in a flowing state. Bulk foam is usually evaluated in a container, specifically by observing the morphology and microscopic size. Since foam exists in an unconfined space, it will coarsen rapidly over time under the influence of drainage, maturation and coalescence effects. Foam has been shown to remain stable for a long time in confined spaces such as microchannels. However, foam oil displacement agents are in a flowing state during application and are a non-Newtonian fluid. During the flow process, they are affected by wall friction and friction between bubbles. In addition, fluid foams themselves have instability and flow regeneration. There is a dynamic balance between rupture and regeneration when fluid foams flow in the pores. The study of polymer-enhanced foams generally focuses on the effect of the increase in the apparent viscosity of foams on oil recovery. From the non-Newtonian behavior described by the power law model, it can be seen that the rheological parameters of foams can be divided into viscosity coefficient (initial viscosity) and power law index (shear resistance). In the study of foam displacement, the effect of rheological properties on the recovery rate should be further examined. Therefore, it is of great practical value to develop polymers that can simultaneously and efficiently enhance the viscosity and shear resistance of foam oil displacement agents. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a polymer and application thereof, which can enhance the shear resistance of CO2 / water foam and significantly improve the recovery rate of foam flooding.
[0005] The invention provides a polymer. The raw materials of the polymer include a monomer solution, a cosolvent, a reducing agent and an initiator. The monomer solution includes 2-acrylamide-2-methylpropane sulfonic acid, vinyl acetate, vinyl pyrrolidone and acrylamide or dimethylaminopropyl acrylamide. In the monomer solution, the mass concentration of 2-acrylamide-2-methylpropane sulfonic acid is 5-12.3wt.%, the mass concentration of vinyl acetate is 4-8.6wt.%, the mass concentration of vinyl pyrrolidone is 0-2.8wt.%, the mass concentration of acrylamide or dimethylaminopropyl acrylamide is 3-9.7wt.%, and the rest is water.
[0006] In some embodiments, in the polymer, certain components and contents have the following definitions, and definitions not mentioned are as described in any embodiment of the present invention (hereinafter referred to as "in some embodiments").
[0007] In some embodiments, the mass ratio of the co-solvent to the monomer solution is 0.12-0.22, for example 0.128.
[0008] In some embodiments, the co-solvent is selected from one or two of ethanol, methanol, dimethyl methylphosphonate, glycerol acetone acetal and dodecyl diethanolamide, such as ethanol.
[0009] In some embodiments, the initiator is ammonium persulfate, azobisisobutyronitrile and N,N,N,N-tetramethylethylenediamine, or ammonium persulfate, azobisisobutyronitrile and sodium bisulfite.
[0010] In some embodiments, the mass ratio of ammonium persulfate, azobisisobutyronitrile and sodium bisulfite is 0.30-0.50:0.15-0.53:0.17-0.4, for example 0.46:0.15:0.39.
[0011] In some embodiments, the mass ratio of ammonium persulfate, azobisisobutyronitrile and N,N,N,N-tetramethylethylenediamine is 0.5-0.6:0.2-0.25:0.2-0.25, for example 0.5:0.25:0.25.
[0012] In some embodiments, the mass ratio of the initiator to the monomer is 0.03-0.07, for example 0.067.
[0013] In some embodiments, the reducing agent is a sodium hydroxide solution or a sodium formate solution, such as a sodium hydroxide solution with a mass concentration of 5%.
[0014] In some embodiments, the mass ratio of the reducing agent to the monomer solution is 0.05-0.17, for example 0.064.
[0015] In some embodiments, the method for preparing the polymer further comprises the following steps:
[0016] The 2-acrylamide-2-methylpropanesulfonic acid and the acrylamide or dimethylaminopropyl acrylamide are dissolved in water, a base is added to adjust the pH to 6-8 (e.g. 7), and the vinyl acetate and the cosolvent are added to prepare a solution A;
[0017] Adding the azobisisobutyronitrile or the sodium bisulfite and the co-solvent to the aqueous solution of the ammonium persulfate and the N,N,N',N'-tetramethylethylenediamine to obtain a solution B;
[0018] After nitrogen is passed through the solution A to deoxygenate (for example, for 20 minutes), solution B is added and nitrogen is continued to be passed through (for example, for 10 minutes); the reaction temperature of the system is controlled to be 50-70° C. (for example, 65° C.), and the reducing agent is added (for example, when the solution begins to become viscous) (react for 3-6 hours) to obtain the product.
[0019] In some embodiments, the method for preparing the polymer further comprises the following post-processing step: the product after the reaction is dialyzed in ethanol and water, freeze-dried, and ground to obtain powder.
[0020] The invention provides a foam, wherein raw materials of the foam include: a foaming solution and CO2; the volume ratio of the foaming solution to CO2 is 1:9; the foaming solution includes an aqueous solution of the polymer described above with a mass fraction of 0.6%, an aqueous solution of cocamidopropyl betaine with a mass fraction of 4%, and the balance is water.
[0021] In some embodiments, in the foam, certain components and contents have the following definitions, and definitions not mentioned are as described in any embodiment of the present invention (hereinafter referred to as "in some embodiments").
[0022] In some embodiments, the method for preparing the foam comprises the following steps: passing the CO2 into the foaming solution and stirring (800 rpm) to obtain (30 min).
[0023] In some embodiments, the foam is prepared as follows Figure 1 shown.
[0024] The present invention provides an application of the foam as described above in core flooding.
[0025] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0026] The reagents and raw materials used in the present invention are commercially available.
[0027] The positive and progressive effects of the present invention are:
[0028] The polymer of the present invention can effectively improve the shear resistance while increasing the viscosity of the foam oil displacement agent, ensure that the foam can maintain high viscosity when flowing in a heterogeneous formation, effectively improve the sweep efficiency of the foam, and thus improve the oil recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of foam preparation, testing and tail liquid collection system.
[0030] Figure 2 is the infrared spectrum of the polymer. DETAILED DESCRIPTION
[0031] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0032] Example 1
[0033] (1) Add 3.19 g of 2-acrylamide-2-methylpropanesulfonic acid, 5.71 g of acrylamide, and 40 g of deionized water to a beaker and stir them with a magnetic stirrer until they are completely dissolved. Then add 2.5 mol / L sodium hydroxide solution to adjust the pH to 7. Then add 5.1 g of vinyl acetate and 10 mL of co-solvent ethanol and stir until they are completely dissolved to prepare solution A.
[0034] (2) In a beaker, add 0.17 g of ammonium persulfate and 0.1 g of sodium bisulfite in turn and stir to dissolve in 5 g of deionized water. Add 0.3 g of azobisisobutyronitrile and 3 mL of co-solvent methanol to obtain solution B.
[0035] (3) Add solution A to the flask, pass nitrogen to deoxygenate for 20 minutes, add solution B, and continue to pass nitrogen for 10 minutes.
[0036] (4) Control the system reaction temperature to 65°C. When the solution begins to become viscous, add 10 ml of sodium hydroxide solution with a reducing agent concentration of 5%. Continue the reaction for 3-6 hours to obtain the product.
[0037] (5) The product was taken out and dialyzed against ethanol and water to remove impurities. The product was freeze-dried and ground to obtain a powder.
[0038] Foam preparation: The mass concentration of surfactant cocamidopropyl betaine in the foaming solution is 4wt%, the mass concentration of polymer is 0.6wt%, and the balance is deionized water. The foam mass is set to 0.9, that is, the solution volume is 10v / v%, the CO2 volume is 90v / v%, CO2 is introduced to 12Mpa, and stirred at a speed of 800rpm for 30min to obtain.
[0039] There is no requirement for the product powder, but in the experimental examples, the maximum particle size after grinding is less than 2 mm.
[0040] Foam rheological behavior test: The prepared 4wt% cocamidopropyl betaine and 0.6wt% polymer aqueous solution were placed in an emulsifier at a ratio of 0.9 to foam mass. 12MPa of CO2 was charged into the emulsifier and stirred at 800rpm for 30min to obtain the specified foam. The experimental pipeline was connected, the tail pressure was set to 12MPa, and the flow rate of the constant flow pump was set. The emulsifier partition pressed the foam into the test section round straight pipe at the set flow rate, and the foam flow pressure difference was obtained.
[0041] The rheological behavior of the foam displacement agent of the present invention is tested by a tubular rheological system. Considering the non-Newtonian characteristics of the shear thinning of the foam fluid, a power law model is used to describe the rheological behavior of the foam fluid. Therefore, the corresponding wall shear stress and wall apparent shear rate are expressed as:
[0042]
[0043]
[0044] ∆P is the pressure difference between the two ends of the test pipe, D is the pipe diameter, L is the length of the test pipe, and u is the foam flow rate.
[0045] The equation for the power law model is as follows:
[0046]
[0047] If the shear stress is the wall shear stress τ w , then the shear rate should be the intrinsic shear rate of the wall γ wi , and its calculation formula is:
[0048]
[0049] The power law exponent n is equal to the parameter n'
[32] and can be calculated as:
[0050]
[0051] The viscosity coefficient K is:
[0052]
[0053] The apparent viscosity of the foam is:
[0054]
[0055] Depend on Figure 2 It can be seen that 3565cm -1 The peak of -OH, 3320 cm -1 is the peak of -NH2, 2940 is the absorption peak of -CH2-, 1670 cm -1 is the stretching vibration peak of primary amide -C=O, 1559 cm -1 The peak at 1490 cm is the deformation vibration peak of -NH. -1 1188 cm -1 SO - The characteristic absorption peak of the 3 group is 1043 cm -1 It is the characteristic absorption peak of -S=O. In summary, the characteristic peaks of AMPS, VA, and AM have all appeared in the figure.
[0056] The foam viscosity coefficient K of the sample prepared in Example 1 is 6.91, and the power law index n is 0.78. The viscosity change is shown in Table 1. The shear viscosity of the polymer-enhanced CO2 / water foam was measured by a tubular rheometer. The flow behavior of the foam was described according to the power law model. The viscosity coefficient K represents the initial viscosity of the foam, and the power law index n represents the shear resistance of the foam.
[0057] Table 1
[0058]
[0059] Example 2
[0060] (1) Add 9.63 g of 2-acrylamide-2-methylpropanesulfonic acid, 2.12 g of vinyl pyrrolidone, 2.71 g of acrylamide, and 50 g of deionized water to a beaker and stir magnetically until completely dissolved. Then add 2.5 mol / L sodium hydroxide solution to adjust the pH to 7. Then add 4.93 g of vinyl acetate and 8 mL of co-solvent ethanol and stir until completely dissolved to obtain solution A.
[0061] (2) Add 0.6 g of ammonium persulfate and 0.5 g of sodium bisulfite to a beaker, stir and dissolve in 8.9 g of deionized water, add 0.2 g of azobisisobutyronitrile and 2 mL of co-solvent ethanol to obtain initiator solution B.
[0062] (3) Add solution A to the flask, pass nitrogen to deoxygenate for 20 minutes, add solution B, and continue to pass nitrogen for 10 minutes.
[0063] (4) Control the system reaction temperature to 65°C. When the solution begins to become viscous, add 5 ml of 5% sodium hydroxide solution. Continue the reaction for 3-6 hours to obtain the product.
[0064] (5) The product was taken out and dialyzed against ethanol and water to remove impurities. The product was freeze-dried and ground to obtain the product polymer powder.
[0065] Foam preparation: The mass concentration of surfactant cocamidopropyl betaine in the foaming solution is 4wt%, the mass concentration of polymer is 0.6wt%, and the balance is deionized water. The foam mass is set to 0.9, that is, the solution volume is 10v / v%, the CO2 volume is 90v / v%, CO2 is introduced to 12Mpa, and stirred at a speed of 800rpm for 30min to obtain.
[0066] There is no requirement for the product powder, but in the experimental example, the maximum particle size after grinding is less than 2 mm. The foam viscosity coefficient K of the sample prepared in Example 2 is 9.27, and the power law index n is 0.72. The viscosity change is shown in Table 2.
[0067] Table 2
[0068]
[0069] Example 3
[0070] (1) Add 4.37 g of 2-acrylamide-2-methylpropanesulfonic acid, 1.61 g of vinyl pyrrolidone, 6.5 g of dimethylaminopropyl acrylamide and 70 g of deionized water to a beaker and stir magnetically until completely dissolved. Then add 2.5 mol / L sodium hydroxide solution to adjust the pH to 7. Then add 7.11 g of vinyl acetate and 12 mL of co-solvent ethanol and stir until completely dissolved to obtain solution A.
[0071] (2) In a beaker, add 0.6 g of ammonium persulfate and 0.3 g of N,N,N',N'-tetramethylethylenediamine in sequence and stir to dissolve in 8.9 g of deionized water. Add 0.3 g of azobisisobutyronitrile and 3 mL of co-solvent methanol to obtain initiator solution B.
[0072] (3) Add solution A to the flask, pass nitrogen to deoxygenate for 20 minutes, add solution B, and continue to pass nitrogen for 10 minutes.
[0073] (4) Control the system reaction temperature to 70°C. When the solution begins to become viscous, add 10 ml of reducing agent. Continue the reaction for 3-6 hours to obtain the product.
[0074] (5) The product was taken out and dialyzed against ethanol and water to remove impurities. The product was freeze-dried and ground to obtain a powder.
[0075] Foam preparation: The mass concentration of surfactant cocamidopropyl betaine in the foaming solution is 4wt%, the mass concentration of polymer is 0.6wt%, and the balance is deionized water. The foam mass is set to 0.9, that is, the solution volume is 10v / v%, the CO2 volume is 90v / v%, CO2 is introduced to 12Mpa, and stirred at a speed of 800rpm for 30min to obtain.
[0076] There is no requirement for the product powder, but in the experimental examples, the maximum particle size after grinding is less than 2 mm.
[0077] The foam viscosity coefficient K of the sample prepared in Example 3 is 7.69, and the power law index n is 0.79. The viscosity change is shown in Table 3.
[0078] Table 3
[0079]
[0080] Example 4
[0081] (1) Add 3.79 g of 2-acrylamide-2-methylpropanesulfonic acid, 1.78 g of vinyl pyrrolidone, 6.09 g of acrylamide and 50 g of deionized water to a beaker and stir magnetically until completely dissolved. Then add 2.5 mol / L sodium hydroxide solution to adjust the pH to 7. Then add 3.11 g of vinyl acetate and 10 mL of co-solvent ethanol and stir until completely dissolved to obtain solution A.
[0082] (2) In a beaker, add 0.3 g of ammonium persulfate and 0.1 g of N,N,N',N'-tetramethylethylenediamine in sequence and stir to dissolve in 8.9 g of deionized water. Add 0.1 g of azobisisobutyronitrile and 3 mL of co-solvent methanol to obtain initiator solution B.
[0083] (3) Add solution A to the flask, pass nitrogen to deoxygenate for 30 minutes, add solution B, and continue to pass nitrogen for 10 minutes.
[0084] (4) Control the system reaction temperature to 70°C. When the solution begins to become viscous, add 7 ml of reducing agent NaOH solution. Continue the reaction for 3-6 hours to obtain the product.
[0085] (5) The product was taken out and dialyzed against ethanol and water to remove impurities. The product was freeze-dried and ground to obtain a powder.
[0086] Foam preparation: The mass concentration of surfactant cocamidopropyl betaine in the foaming solution is 4wt%, the mass concentration of polymer is 0.6wt%, and the balance is deionized water. The foam mass is set to 0.9, that is, the solution volume is 10v / v%, the CO2 volume is 90v / v%, CO2 is introduced to 12Mpa, and stirred at a speed of 800rpm for 30min to obtain.
[0087] There is no requirement for the product powder, but in the experimental examples, the maximum particle size after grinding is less than 2 mm.
[0088] The foam viscosity coefficient K of the sample prepared in Example 4 is 7.11, and the power law index n is 0.61. The viscosity change is shown in Table 4.
[0089] Table 4
[0090]
[0091] Comparative Example 1
[0092] 4% cocamidopropyl betaine, 0.6% poly(2-acrylamide-2-methylpropanesulfonic acid) (poly(2-acrylamide-2-methylpropanesulfonic acid) provided by Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 15214-89-8; Product No.: A800508), and the balance is deionized water. The foam mass is set to 0.9, that is, the solution volume is 10v / v%, the CO2 volume is 90v / v%, and CO2 is introduced to 12Mpa, and stirred at a speed of 800rpm for 30min to obtain.
[0093] There is no requirement for the product powder, but in the experimental examples, the maximum particle size after grinding is less than 2 mm.
[0094] The foam viscosity coefficient K of the sample prepared in Comparative Example 1 is 10.19, and the power law index n is 0.59. The viscosity change is shown in Table 5.
[0095] Table 5
[0096]
[0097] Comparative Example 2 4% mass fraction of cocamidopropyl betaine, 0.6% mass fraction of polyacrylamide (non-ionic polyacrylamide provided by Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 9003-05-8; Article No.: P875616), and the balance is deionized water. The foam mass is set to 0.9, that is, the solution volume is 10v / v%, the CO2 volume is 90v / v%, and CO2 is introduced to 12Mpa, and stirred at a speed of 800rpm for 30min to obtain.
[0098] There is no requirement for the product powder, but in the experimental examples, the maximum particle size after grinding is less than 2 mm.
[0099] The foam viscosity coefficient K of the sample prepared in Comparative Example 2 is 1.22, and the power law index n is 0.52. The viscosity change is shown in Table 6.
[0100] Table 6
[0101]
[0102] Effect Example 1 Core flooding test
[0103] The viscosity improvement of polymer enhanced foam contributes to the recovery rate of foam displacement, and generally, the higher the foam viscosity, the higher the sweep efficiency of the foam. The polymer enhanced foam of the present invention has high viscosity at low shear rates, which ensures its plugging ability in the formation; and has strong shear resistance, and can still maintain high viscosity at high shear rates, which ensures its sweep ability in heterogeneous reservoirs. However, the oil recovery rate of the foam prepared by the polymer in heterogeneous reservoirs should be further verified. Therefore, the inventors conducted oil displacement tests on the polymer enhanced foams in the embodiments and comparative examples at 12MPa and 30°C.
[0104] The core with a permeability of 121 mDa was saturated with oil and placed in a core holder, and the confining pressure was set to 15 MPa in the outer ring to simulate the formation pressure. After connecting all the pipelines, the tail pressure was set to 12 MPa at the end of the displacement path to maintain a constant system pressure, and the foam prepared in Example 1-6 was used to start displacement. When the average water content of the outlet liquid exceeded 98%, the displacement was stopped and the oil recovery factor was calculated. The final results are shown in Table 6.
[0105] Table 7
[0106]
[0107] As can be seen from Table 7, the polymer-enhanced foam of the present invention can effectively improve oil recovery in heterogeneous reservoirs. Experiments show that the increase in viscosity coefficient can further increase the initial viscosity of the foam, while the increase in power law exponent enhances the shear resistance of the foam, that is, the viscosity retention rate. The increase in initial viscosity and shear resistance of the polymer-enhanced foam helps to improve the recovery rate of foam displacement, and the increase in shear resistance further improves the sweep efficiency of the foam compared to the initial viscosity.
[0108] Experiments show that improving the viscosity and shear resistance of polymer-enhanced foams helps to improve the recovery rate of foam displacement, and the better the shear resistance, the higher the foam sweep efficiency. The adsorption behavior of polymers at the interface and liquid phase determines the rheological properties of foam flooding agents. It is difficult for existing traditional polymers to improve the shear resistance of foams while increasing viscosity.
[0109] The above is an exemplary description of the present invention, but it does not limit the present invention. Without departing from the scope of the technical solution of the present invention, the technical contents disclosed above can be used to make some changes or modifications to equivalent embodiments with equivalent changes. However, any simple modification, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A polymer, characterized in that The raw materials of the polymer include a monomer solution, a cosolvent, a reducing agent and an initiator; the monomer solution includes 2-acrylamide-2-methylpropane sulfonic acid, vinyl acetate, vinyl pyrrolidone and acrylamide or dimethylaminopropyl acrylamide; in the monomer solution, the mass concentration of 2-acrylamide-2-methylpropane sulfonic acid is 5-12.3wt.%, the mass concentration of vinyl acetate is 4-8.6wt.%, the mass concentration of vinyl pyrrolidone is 0-2.8wt.%, the mass concentration of acrylamide or dimethylaminopropyl acrylamide is 3-9.7wt.%, and the rest is water.
2. The polymer according to claim 1, characterized in that The polymer satisfies one or more of the following conditions: (1) The mass ratio of the co-solvent to the monomer solution is 0.12-0.22; (2) The co-solvent is selected from one or two of ethanol, methanol, dimethyl methylphosphonate, glycerol acetone acetal and dodecyl diethanolamide; (3) The initiator is ammonium persulfate, azobisisobutyronitrile and N,N,N,N-tetramethylethylenediamine, or ammonium persulfate, azobisisobutyronitrile and sodium bisulfite; (4) The mass ratio of the initiator to the monomer is 0.03-0.07; (5) The reducing agent is sodium hydroxide solution or sodium formate solution; (6) The mass ratio of the reducing agent to the monomer solution is 0.05-0.17; The preparation method of the polymer described in (7) further comprises the following post-treatment step: the product after the reaction is dialyzed in ethanol and water, freeze-dried, and ground to obtain powder.
3. The polymer according to claim 2, characterized in that The polymer satisfies one or more of the following conditions: (1) The mass ratio of the co-solvent to the monomer solution is 0.128; (2) The cosolvent is ethanol; (3) The mass ratio of ammonium persulfate, azobisisobutyronitrile and sodium bisulfite is 0.30-0.50:0.15-0.53:0.17-0.4; (4) The mass ratio of ammonium persulfate, azobisisobutyronitrile and N,N,N,N-tetramethylethylenediamine is 0.5-0.6:0.2-0.25:0.2-0.25; (5) The mass ratio of the initiator to the monomer is 0.067; (6) The reducing agent is a sodium hydroxide solution with a mass concentration of 5%; and (7) the mass ratio of the reducing agent to the monomer solution is 0.
064.
4. The polymer according to claim 3, characterized in that The mass ratio of the ammonium persulfate, azobisisobutyronitrile and sodium bisulfite is 0.46:0.15:0.39, or the mass ratio of the ammonium persulfate, azobisisobutyronitrile and N,N,N,N-tetramethylethylenediamine is 0.5:0.25:0.
25.
5. The polymer according to any one of claims 2 to 3, characterized in that The 2-acrylamide-2-methylpropanesulfonic acid and the acrylamide or dimethylaminopropyl acrylamide are dissolved in water, a base is added to adjust the pH to 6-8, and the vinyl acetate and the cosolvent are added to prepare a solution A; Adding the azobisisobutyronitrile or the sodium bisulfite and the co-solvent to the aqueous solution of the ammonium persulfate and the N,N,N',N'-tetramethylethylenediamine to obtain a solution B; After nitrogen is passed through the solution A to deoxygenate, solution B is added and nitrogen is continued to be passed through; the reaction temperature of the system is controlled to be 50-70° C., and the reducing agent is added to obtain the product.
6. The polymer according to claim 5, characterized in that The 2-acrylamide-2-methylpropanesulfonic acid and the acrylamide or dimethylaminopropyl acrylamide are dissolved in water, a base is added to adjust the pH to 7, and the vinyl acetate and the cosolvent are added to prepare a solution A; Adding the azobisisobutyronitrile or the sodium bisulfite and the co-solvent to the aqueous solution of the ammonium persulfate and the N,N,N',N'-tetramethylethylenediamine to obtain a solution B; After nitrogen was passed through the solution A for 20 minutes to deoxygenate, the solution B was added and nitrogen was continued to be passed through for 10 minutes. The reaction temperature of the system was controlled at 65° C. When the solution began to become viscous, the reducing agent was added and reacted for 3-6 hours to obtain the product.
7. A foam, characterized in that The raw materials of the foam include: a foaming solution and CO2; the volume ratio of the foaming solution and CO2 is 1:9; the foaming solution includes a 0.6% by mass aqueous solution of the polymer as described in any one of claims 1 to 6, a 4% by mass aqueous solution of cocamidopropyl betaine, and the remainder is water.
8. The foam according to claim 7, characterized in that The method for preparing the foam comprises the following steps: passing the CO2 into the foaming solution and stirring to obtain the foam; And / or, the preparation process of the foam is as shown in FIG1 .
9. The foam according to claim 8, characterized in that The method for preparing the foam comprises the following steps: introducing the CO2 into the foaming solution and stirring at 800 rpm for 30 minutes to obtain the foam.
10. Use of the foam according to any one of claims 7 to 9 in core flooding.